Nitrovasodilators, Low-Dose Aspirin, Other Nonsteroidal Antiinflammatory Drugs, and the Risk of Upper Gastrointestinal Bleeding - Lanas, Angel; Bajador, Eduardo; Serrano, Pedro; Fuentes, Javier; Carreño, Sofía; Guardia, Jesusa; Sanz, Mercedes; Montoro, Miguel; Sáinz, Ricardo (The New England journal of medicine, 2000)
Nonsteroidal antiinflammatory drugs, including low-dose aspirin, induce gastrointestinal complications. 1 – 3 Although new and potentially safer nonsteroidal antiinflammatory drugs (such as cyclooxygenase-2 inhibitors) are now in use, 4 it is uncertain whether these new drugs will reduce the number of patients hospitalized with gastrointestinal bleeding. Over-the-counter nonsteroidal antiinflammatory drugs, especially aspirin, are the drugs most frequently associated with bleeding, 5 and the number of people taking low-dose aspirin is increasing. 3 Nonsteroidal antiinflammatory drugs that release nitric oxide are under investigation. 6 , 7 Nitric oxide increases blood flow in the gastric mucosa and inhibits the adherence of leukocytes to the endothelium within the gastrointestinal microcirculation. . . .